Phytochemistry, Pharmacology and Medicinal Uses of Plants of the Genus Salix: An Updated Review - Tawfeek, Nora; Mahmoud, Mona F.; Hamdan, Dalia I; Sobeh, Mansour; Farrag, Nawaal; Wink, Michael; El-Shazly, Assem M. (Frontiers in Pharmacology, 2021)
The Willows (genus Salix), with more than 330–500 species and 200 hybrids, are trees, shrubs or prostrate plants that are widely distributed in Africa, North America, Europe, and Asia. The genus is traditionally used in folk medicine and represents a valuable source of biologically active compounds among them salicin, a prodrug for salicylic acid. Altogether, 322 secondary metabolites were characterized in the genus including flavonoids (94) (flavonols, flavones, flavanones, isoflavones, flavan-3-ols (catechins and procyanidins), chalcones, dihydrochalcone, anthocyanins, dihydroflavonols), phenolic glycosides (76), organic acids (28), and non-phenolic glycosides (17), sterols and terpenes (17), simple phenolics (13) and lignans (7) in addition to volatiles and fatty acids (69). Furthermore, willows exert analgesic, anti-inflammatory, antioxidant, anticancer, cytotoxic, antidiabetic, antimicrobial, antiobesity, neuroprotective and hepatoprotective activities. The current review provides an updated summary of the importance of willows, their chemical composition, and pharmacological activities.